Radiofrequency ablation versus resection for Barcelona clinic liver cancer very early/early stage hepatocellular carcinoma: a systematic review - He ZX; Xiang P; Gong JP; Cheng NS; Zhang W (Therapeutics and Clinical Risk Management, 2016)
Zhen-Xin He,1 Pu Xiang,2 Jian-Ping Gong,1 Nan-Sheng Cheng,3 Wei Zhang4 1Department of Hepatobiliary Surgery, the Second Affiliated Hospital, Chongqing Medical University, Chongqing, 2State Key Laboratory of Biotherapy and Cancer Center, 3Department of Bile Duct Surgery, West China Hospital, Sichuan University, Chengdu, 4Department of Hepatobiliary Surgery, Yue Bei People’s Hospital, Shaoguan, Guangdong, People’s Republic of China Aim: To compare the long-term survival outcomes of radiofrequency ablation and liver resection for single very early/early stage hepatocellular carcinoma (HCC). Methods: The Cochrane Library (Issue 3, 2015), Embase (1974 to March 15, 2015), PubMed (1950 to March 15, 2015), Web of Science (1900 to March 15, 2015), and Chinese Biomedical Literature Database (1978 to March 15, 2015) were searched to identify relevant trials. Only trials that compared radiofrequency ablation and liver resection for single very early stage (≤2 cm) or early stage (≤3 cm) HCC according to the Barcelona clinic liver cancer (BCLC) staging system were considered for inclusion in this review. The primary outcomes that we analyzed were the 3-year and 5-year overall survival (OS) rates, and the secondary outcomes that we analyzed were the 3-year and 5-year disease-free survival (DFS) rates. Review Manager 5.3 was used to perform a cumulative meta-analysis. Possible publication bias was examined using a funnel plot. A random-effects model was applied to summarize the various outcomes. Results: Six studies involving 947 patients were identified that compared radiofrequency ablation (n=528) to liver resection (n=419) for single BCLC very early HCC. In these six studies, the rates of 3-year OS, 5-year OS, 3-year DFS, and 5-year DFS were significantly lower in the radiofrequency ablation group than in the liver resection group (risk ratio [RR] =0.90, 95% confidence interval [CI]: 0.83–0.98, P=0.01; RR =0.84, 95% CI: 0.75–0.95, P=0.004; RR =0.77, 95% CI: 0.60–0.98, P=0.04; and RR =0.70, 95% CI: 0.52–0.94, P=0.02, respectively). Ten studies involving 2,501 patients were identified that compared radiofrequency ablation (n=1,476) to liver resection (n=1,025) for single BCLC early HCC. In these ten studies, the rates of 3-year OS, 5-year OS, 3-year DFS, and 5-year DFS were also significantly lower in the radiofrequency ablation group than in the liver resection group (RR =0.93, 95% CI: 0.88–0.98, P=0.003; RR =0.84, 95% CI: 0.75–0.94, P=0.002; RR =0.72, 95% CI: 0.58–0.89, P=0.002; and RR =0.47, 95% CI: 0.33–0.67, P<0.0001, respectively).Conclusion: The long-term survival outcomes for patients with single BCLC very early/early stage HCC appear to be superior after liver resection compared to radiofrequency ablation. Keywords: radiofrequency ablation, liver resection, hepatocellular carcinoma, systematic review